Pengaruh Job Crafting terhadap Kreativitas melalui Work ENgagement sebagai Variabel Mediasi - Nur Aini (Jurnal Ilmu Manajemen, 2022)
This study aims to examine the relationship between job crafting and creativity. It also examined whether work engagement mediated the relationship between job crafting and creativity. This research was causal research that used a quantitative approach by collecting data using questionnaire. In this study, the sample was 60 employees of Bank. The analytical method used in this research was partial least squares (PLS) using Smart PLS 3.0 software.The Likert Scale is used as a measurement scale. The results of the model equation test showed that job crafting had a significant effect on creativity. Job crafting had a significant effect on work engagement. Work engagement had no significant effect on creativity. In addition, work engagement as a mediating variable had no significant effect on the relationship between job crafting and creativity. The managerial implication of this study, the company could improve employees’ job crafting so that employees had more potential to produce creativity at work.